Behaviour of the Mg ii 2798 Å line over the full range of AGN variability. Issue 1 (30th May 2020) - Homan, David; MacLeod, Chelsea L; Lawrence, Andy; Ross, Nicholas P; Bruce, Alastair
ABSTRACT: We investigate the responsiveness of the 2798 Å Mg ii broad emission line in active galactic nuclei (AGNs) on time-scales of several years. Our study is based on a sample of extremely variable AGNs as well as a broad population sample. The observed response of the line in previous studies has been mixed. By focusing on extreme variability (|Δ g | > 1), we find that Mg ii clearly does respond to the continuum. However, the degree of responsiveness varies strikingly from one object to another: We see cases of Mg ii changing by as much as the continuum, more than the continuum, or very little at all. In 74 per cent of the highly variable sample, the behaviour of Mg ii corresponds with that of H β, with 30 per cent of the objects showing large variations in both lines. We do not detect any change in the line width that would correspond to broad-line region 'breathing', in accordance with results from the literature. Some of the objects in our highly variable sample show a clear asymmetry in the Mg ii profile. This skewness can be both to the blue and the red of the line centre. Results from our broad population sample show that highly variable quasars have lower Eddington ratios. This result holds for the variability of the continuum, but the correlation is significantly reduced for the variability of the Mg ii line. For the first time, we present an overview of the value of the intrinsic Baldwin effect for Mg ii in a large sample.